Current Diagnosis and Management of Pelvic Fistulae in Women. Issue 3 (September 2016) - Rogers, Rebecca G.; Jeppson, Peter C.
Abstract : Pelvic fistulae are an abnormal communication among the genitourinary tract, the gastrointestinal tract, and the vagina or perineum. Genital tract fistulae have been described in the medical literature for the past several thousand years. Advancements in both the diagnosis and treatment of vaginal fistulae have been obtained over the past century as surgical interventions have become safer and surgical techniques have improved. The most common cause of fistulae worldwide is obstructed labor. In developed countries, fistulae most commonly occur after benign gynecologic surgery, but obstructed labor, malignancy, radiation exposure, and inflammatory bowel disease can also cause fistulae. Fistulae significantly affect quality of life. Diagnostic studies and radiologic imaging can help aid the diagnosis, but a thorough physical examination is the most important component in the evaluation and diagnosis of a fistula. Temporizing treatments are available to help ease patient suffering until surgical management can be performed. Surgical repairs can be performed using an abdominal, vaginal, or transanal approach. Although technically challenging, surgical repair is usually successful, but closure of the fistula tract does not guarantee continence of urine or feces, because there is often underlying damage to the bowel and bladder. Abstract : Supplemental Digital Content is Available in the Text.A review of the evaluation and treatment of vaginal fistulae is presented.